1999
DOI: 10.1063/1.370993
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependence of the crystallization of Ba-ferrite films

Abstract: The crystallization of Ba-ferrite/sapphire(001) films of various thicknesses has been studied using synchrotron x-ray scattering, field emission scanning electron microscope, and atomic force microscope. In films thinner than 1000 Å, Ba-ferrite amorphous precursor was crystallized into perpendicular grains keeping the magnetically easy c-axis normal to the film plane during annealing to 750 °C. In films thicker than 1000 Å, however, acicular grains keeping the c-axis parallel to the film plane were grown on to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Hexagonal barium ferrite, BaFe 12 O 19 ; has been extensively investigated because it is a promising candidate for future high-density recording media as well as having microwave-linked applications [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The large coercivity, corrosion resistance, and high chemical stability of barium ferrite has also led to its widespread use in permanent magnets and recording materials.…”
Section: Introductionmentioning
confidence: 99%
“…Hexagonal barium ferrite, BaFe 12 O 19 ; has been extensively investigated because it is a promising candidate for future high-density recording media as well as having microwave-linked applications [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The large coercivity, corrosion resistance, and high chemical stability of barium ferrite has also led to its widespread use in permanent magnets and recording materials.…”
Section: Introductionmentioning
confidence: 99%
“…Concomitantly, we have observed that the increase in sputtering power/thickness of the film tends to align the magnetization parallel to the sample plane. The work by Cho et al [40] had already pointed out the dependence of the magnetization with the film thickness for barium ferrite, BFO (which is isostructural with SFO) on sapphire (001). In that study, they found that at thicknesses less than 100 nm, the BFO grains grew perpendicular to the substrate surface with the c-axis out-of-plane, while at larger thicknesses elongated grains grew at the top of the columnar grains parallel to the surface substrate, their c-axis lying also parallel to the surface plane.…”
Section: Resultsmentioning
confidence: 99%
“…The mosaic distribution, which is usually studied by measuring the FWHM in the theta (θ )-rocking curve of Bragg reflection, represents the epitaxial quality of a thin film [10,11]. The mosaic distribution of the as-deposited ZnO films with a 2400-Å-thick was composed of the sharp and the broad components with about 0.02 • and 1.86 • FWHMs, respectively (data not shown).…”
Section: Resultsmentioning
confidence: 99%